2022
DOI: 10.1037/tra0001084
|View full text |Cite
|
Sign up to set email alerts
|

Cross-lagged analyses of anger and PTSD symptoms among veterans in treatment.

Abstract: Objective: Anger is a salient feature of posttraumatic mental health which is linked to posttraumatic stress disorder (PTSD) and may have implications for treatment. However, the nature of associations involving anger and PTSD remains unclear. The aim of the present study was to examine bidirectional influences involving anger and International Classification of Diseases (ICD)-11 PTSD symptom clusters over time among treatment-seeking veterans. Method: Current or ex-serving members (n = 742; 92.4% male) who pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, studies have also found that changes in specific trauma appraisals are associated with or even predict changes in PTSD (e.g. Cowlishaw et al, 2022 ; Foa & Rauch, 2004 ; Ginzburg et al, 2009 ; Görg et al, 2017 ) in different trauma samples receiving trauma-focused treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have also found that changes in specific trauma appraisals are associated with or even predict changes in PTSD (e.g. Cowlishaw et al, 2022 ; Foa & Rauch, 2004 ; Ginzburg et al, 2009 ; Görg et al, 2017 ) in different trauma samples receiving trauma-focused treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a benefit of anger interventions was found in subjects with anger problems. You can therefore also benefit from such interventions before starting trauma-specific therapy ( 60 ) because anger has been shown to be a relevant factor in PTSD therapy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings that anger is highly correlated with other PTSD symptoms and accounts for a substantial proportion of the variance in total PTSD symptom severity (Durham et al., 2018). In addition, anger appears to exacerbate reexperiencing, avoidance, and hyperarousal symptoms of PTSD over a period of months (Cowlishaw et al., 2022), whereas there is evidence for effects in the opposite direction when measured over a period of hours (Van Voorhees et al., 2018). Importantly, anger has also been shown to mediate the longitudinal association between PTSD symptoms and suicidal ideation in military veterans (Dillon et al., 2020), potentially via consequences of anger, such as interpersonal conflict and reduced social support (Diong et al., 2005).…”
Section: Ptsd and Relationship Functioningmentioning
confidence: 99%